2017
DOI: 10.1016/j.hal.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Species occurrence of the potentially toxigenic diatom genus Pseudo-nitzschia and the associated neurotoxin domoic acid in the Argentine Sea

Abstract: Keywords:Amnesic shellfish poisoning South-western Atlantic Pseudo-nitzschia diversity P. australis P. brasiliana Domoic acid A B S T R A C TThe marine diatom genus Pseudo-nitzschia, the major known producer of the neurotoxin domoic acid (DA) responsible for the amnesic shellfish poisoning (ASP) syndrome in humans and marine mammals, is globally distributed. The genus presents high species richness in the Argentine Sea and DA has been frequently detected in the last few years in plankton and shellfish samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 53 publications
4
39
0
1
Order By: Relevance
“…Distribution along the entire Argentine coast has been reported for P. pungens (Balech, 1976;Lange, 1985; R.M. Negri and Inza, 1998;Ferrario et al, 1999Ferrario et al, , 2002Gayoso, 2001;Sastre et al, 2001;Sar et al, 2006;Almandoz et al, 2007Almandoz et al, , 2017Sunesen et al, 2009;Cadaillón, 2012;Krock et al, 2015a).…”
Section: Amnesic Shellfish Poisoning (Asp)mentioning
confidence: 93%
See 2 more Smart Citations
“…Distribution along the entire Argentine coast has been reported for P. pungens (Balech, 1976;Lange, 1985; R.M. Negri and Inza, 1998;Ferrario et al, 1999Ferrario et al, , 2002Gayoso, 2001;Sastre et al, 2001;Sar et al, 2006;Almandoz et al, 2007Almandoz et al, , 2017Sunesen et al, 2009;Cadaillón, 2012;Krock et al, 2015a).…”
Section: Amnesic Shellfish Poisoning (Asp)mentioning
confidence: 93%
“…The next species to be reported was Pseudo-nitzschia australis in the San Matías Gulf (41°S; Frenguelli, 1939), which later turned out also to be present in the entire Argentine Sea (Hasle, 1965;Lange, 1985) as P. pseudoseriata (Ferrario and Galván, 1989;Sastre et al, 1997Sastre et al, , 2001R.M. Negri and Inza, 1998;Sar et al, 1998;Ferrario et al, 1999Ferrario et al, , 2002Ferrario et al, , 2017Montoya et al, 2000;Santinelli et al, 2002;Almandoz et al, 2007Almandoz et al, , 2011Almandoz et al, , 2017Cadaillón, 2012;Krock et al, 2015a).…”
Section: Amnesic Shellfish Poisoning (Asp)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study the identification of a bloom of P. australis in net tow samples, and the high cell densities of this species observed in bottle samples in Golfo Nuevo in October, suggest that this species was the main producer of the highest levels of domoic acid. In the Argentine Sea, P. australis has been suggested to be the major producer of domoic acid (Almandoz et al ). Furthermore, P. australis is considered to be a strong domoic acid producer (12–37 pg cell –1 ; Bates ; Kotaki et al ), and for this reason it has been reported to be the most toxic species of the genus Pseudo‐nitzschia (Trainer et al ) and to be primarily responsible for ASP problems worldwide (Bates ; Fire et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P. australis is considered to be a strong domoic acid producer (12–37 pg cell –1 ; Bates ; Kotaki et al ), and for this reason it has been reported to be the most toxic species of the genus Pseudo‐nitzschia (Trainer et al ) and to be primarily responsible for ASP problems worldwide (Bates ; Fire et al ). Therefore, it is worth highlighting the simultaneous detection of the highest levels of domoic acid and major densities of P. australis in the Argentine Sea (Negri and Inza ; Sastre et al ; Negri et al ; Almandoz et al , ) because proliferation of this species may pose a risk for fishery activities in the region that are focused on the Tehuelche scallop ( Aequipecten tehuelchus ) in Golfo San José (Orensanz et al ) and on several species of marine animals that feed and reproduce in both gulfs.…”
Section: Discussionmentioning
confidence: 99%